PENGEMBANGAN MODUL PEMBELAJARAN ETNOPEDAGOGI BERBASIS KEARIFAN LOKAL SUKU SASAK PADA MATA PELAJARAN IPAS KELAS III DI SDN GUGUS III PRAYA - Arafina, Baiq Samia; Asrin; Sobri, Muhammad; Astria, Fitri Puji (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop an ethnopedagogy-based learning module incorporating the local wisdom of the Sasak Tribe for the IPAS subject in grade III of elementary school. The research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations and questionnaires. Observations were conducted during the analysis phase to identify the needs and conditions at SDN 11 Praya and SDN 3 Praya, while questionnaires were used to gather data from expert validators, teachers, and students regarding the validity and practicality of the module. Data analysis was carried out using both qualitative and quantitative approaches. Qualitative data were analyzed based on suggestions and feedback from validators for module revision, while quantitative data were derived from validation and response questionnaire scores, which were analyzed by calculating the average scores and feasibility percentages. The validation results showed that the module obtained scores of 97.9% from material experts and 97.5% from media experts, both categorized as very valid. The practicality test results showed scores of 94.4% from students (small group), 96% from students (large group), and 85.3% from teachers, all categorized as very practical. Based on these results, the ethnopedagogy-based learning module incorporating Sasak local wisdom is proven to be valid and practical, and is suitable for use in grade III IPAS learning to enhance students’ understanding of local cultural contexts.